Antecedents and Consequence of Work-Life Balance - Tamang, Gyan Bahadur (PYC Nepal Journal of Management, 2010)
This paper is originally presented at the “International Seminar on Management” on “Enhancing Enterprise Effectiveness for Global Challenges” organised by Brihaspati College, Siddharthnagar on 3rd and 4th April 2010. The author acknowledges that the printed version of the paper has come after the suggestions from the Editorial Committee. The study examines the work life balance and its cause and effect through a survey conducted during 2008 in nine different stars hotels of Kathmandu, Nepal. Employees of these hotels were surveyed to determine the level of work and family stressors as antecedents, balancing between work and family, and organizational commitment as consequence of work life balance. Descriptive statistics were used to explore the condition of work life balance. Regression analysis was also used to examine the cause and effect relationship of work life balance. The study found low level of stressors of both domains indicating low level of their demand and good balance between work and family. The study also found employees of hospitality industry were highly committed towards their hotels. Role ambiguity alone from work domain was found that affect negatively on work life balance and others’ effect were found statistically insignificant and positive as well. The positive ad statistically significant effect of Hours spend on household work was found on work life balance. Finally the study found work life balance was a good predictor of organizational commitment.